Hemoglobin and Its Scavenger Protein Haptoglobin Associate with ApoA-1-containing Particles and Influence the Inflammatory Properties and Function of High Density Lipoprotein - Watanabe, Junji (American Society for Biochemistry and Molecular Biology, 2009)
Hemoglobin (Hb) uniquely associates with proinflammatory HDL in atherogenic mice and coronary heart disease (CHD) patients. In this paper, we report that Hb and its scavenger proteins, haptoglobin (Hp) and hemopexin (Hx) are significantly increased in apoA-1-containing particles of HDL both in mouse models of hyperlipidemia and in CHD patients, when compared with wild type mice and healthy donors, respectively. We further demonstrate that the association of Hb, Hp, and Hx proteins with HDL positively correlates with inflammatory properties of HDL and systemic inflammation in CHD patients. Interestingly, HDL from Hp(−/−) mice under atherogenic conditions does not accumulate Hb and is anti-inflammatory, suggesting that (i) Hp is required for the association of Hb with HDL and (ii) Hb·Hp complexes regulate the inflammatory properties of HDL. Moreover, treatment of apoE(−/−) mice with an apoA-1 mimetic peptide resulted in significant dissociation of Hb·Hp complexes from HDL and improvement of HDL inflammatory properties. Our data strongly suggest that HDL can become proinflammatory via the Hb·Hp pathway in mice and humans, and dissociation of Hb·Hp·Hx complexes from apoA-1-containing particles of HDL may be a novel target for the treatment of CHD.